(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
As a result of global climate change, Uzbekistan is observing an increase in air temperature, a decrease in precipitation levels, uneven distribution of rainfall during the plant vegetation period, and a reduction in the number of snowy days in winter. On rainfed lands, a significant difference in the heading phase was observed among wheat variety samples, new varieties, and lines. Although early heading in the studied varieties indicates early maturity, it was found that this leads to lower yields compared to latematuring varieties. However, some early-heading varieties were observed to have high grain yields. New varieties of Bread Wheat, such as KSI-96/2024/Sp-1/447/2021 (Tagob), KSI-97/2024/Sp-1/834/2021 (Zartepa), and the line Sp-1/382/2021 (earlyripe), were found to have higher grain yields compared to the early-ripening standard variety, despite heading earlier than this variety. Furthermore, during the studies, it was determined that a higher number of grains per spike and a greater weight of 1000 grains contribute more significantly to increased yield compared to other productivity elements